2016
DOI: 10.1017/cjn.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation Target Selection for Parkinson’s Disease

Abstract: During the "DBS Canada Day" symposium held in Toronto July 4-5, 2014, the scientific committee invited experts to discuss three main questions on target selection for deep brain stimulation (DBS) of patients with Parkinson's disease (PD). First, is the subthalamic nucleus (STN) or the globus pallidus internus (GPi) the ideal target? In summary, both targets are equally effective in improving the motor symptoms of PD. STN allows a greater medications reduction, while GPi exerts a direct antidyskinetic effect. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 68 publications
0
24
0
1
Order By: Relevance
“…A number of studies are beginning to suggest that a staged approach is not necessarily superior to a simultaneous approach; Tanei et al found no statistical significance in the rate of adverse events and found comparable improvements in Unified Parkinson's Disease Rating Scale (UPDRS) scores . Honey et al's (2016) report of “DBS Canada Day Symposium” determined that no convincing evidence has yet been found to advocate for staging . Cost is also similar .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies are beginning to suggest that a staged approach is not necessarily superior to a simultaneous approach; Tanei et al found no statistical significance in the rate of adverse events and found comparable improvements in Unified Parkinson's Disease Rating Scale (UPDRS) scores . Honey et al's (2016) report of “DBS Canada Day Symposium” determined that no convincing evidence has yet been found to advocate for staging . Cost is also similar .…”
Section: Introductionmentioning
confidence: 99%
“…; Bohnen and Jahn ); (iv) Initial studies, although still controversial (Honey et al . ), suggest that deep brain stimulation of the PPN improves postural and gait difficulties in PD patients (Plaha and Gill ; Stefani et al . ; Wilcox et al .…”
mentioning
confidence: 99%
“…The subthalamic nucleus (STN) and internal globus pallidus are the most common targets for deep brain stimulation treatment (DBS) in patients suffering from Parkinson's disease (PD). The effect on motor symptoms in advanced stage of PD are comparable [1][2][3] . Detailed segmentation of the subthalamic nucleus has been the object of several studies.…”
Section: Introductionmentioning
confidence: 82%